New collision detection method for simulating virtual plant populations - Ding, Weilong; Wan, Zangxin; Xu, Yan; Max, Nelson (International Journal of Agricultural and Biological Engineering, 2019)
Detecting and resolving the collision of organs between different plants or the collision of different organs of a single plant are key issues in the realistic construction of a virtual plant population. A suitable collision detection scheme is necessary to prevent a reduction in realism caused by organ penetration. A mixed bounding volume tree construction scheme based on the growth characteristics of tomato plants is proposed in this paper, and the construction mode of the bounding at all levels is simplified by using a digital tomato model. Using a parallel GPU approach, we designed a tomato plant population collision detection program with CUDA acceleration. The proposed method reduces the total collision detection time by 92%-96%.Keywords: plant simulation, collision detection, bounding volume, GPU processingDOI: 10.25165/j.ijabe.20191206.4888Citation: Ding W L, Wan Z X, Xu Y, Max N. New collision detection method for simulating virtual plant populations. Int J Agric & Biol Eng, 2019; 12(6): 156–151.